Place : a short introduction - Cresswell, Tim. (Malden, MA : Blackwell Pub., 2004)
"Place is one of the most fundamental concepts in human geography. This short introduction marries familiar everyday uses of the term with the more complex theoretical debates that have grown up around it." "The text makes the debates intelligible to students, using illustrations from the news, popular culture, and everyday life as a way into more abstract ideas. It traces the development of the concept of place from the 1950s through its subsequent appropriation by cultural geography and the linking of place to politics. Substantial parts of exemplary papers by Doreen Massey and David Harvey are included as a focus for discussion, and the author also considers empirical examples of ways in which the concept of place has been mobilized in research." "Teaching and learning aids include an annotated bibliography, lists of key readings and texts, a survey of web resources, and suggestions for pedagogical resources and student projects. Book jacket."--BOOK JACKET.
-- Introduction: Defining place -- The genealogy of place -- Reading 'a global sense of place' -- Working with place -- Place resources.
Includes bibliographical references (pages [145]-150) and index.
Keywords: Human geography; Geographical perception